MANAJEMEN SUMBER DAYA {BIAYA SARANA DAN PRASARANA PADA SDN CIJANKAR 2} - Fany Cantikasari, Neng Rani Fauziyah, Adi Rosadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Facilities and Infrastructure Planning at SDN Cijangkar 2 is an integral aspect in the implementation of education which always refers to educational facility standards regulated by the applicable PERPU framework. SDN Cijangkar 2 confirms its commitment to providing a high quality and supportive learning environment for its students and staff. The method used in the research is qualitative research with a descriptive approach that uses collection in the form of observations, interviews and documentation studies. In this context, this research aims to investigate strategies and practices for managing facility and infrastructure costs in educational institutions, especially at SDN Cijangkar 2 with a focus on identifying factors that influence the success of this management and its implications for the efficiency and effectiveness of learning.